EVALUASI KEBIJAKAN PAJAK BAHAN GALIAN GOLONGAN C DI KABUPATEN DONGGALA - Latifa, Latifa (Katalogis, 2019)
This research aims to analyze how the evaluation of tax policy of Group C Minerals in Donggala Regency is. The type of research used was qualitative method. This type of research used descriptive approach, research that aims to describe complex social realities in society, is very suitable for understanding and describing social phenomena that occur in society. Data collection was done through observation, interview, and documentation techniques. The data used in this research was primary data by conducting in-depth direct interviews with employees who are competent in this matter and secondary data retrieval obtained from documents in the Regional Revenue Agency of Donggala Regency. Data analysis in this research used three components consisting of data reduction, data presentation and conclusion. The results of this research indicate that the evaluation of tax policy of Group C minerals has not been maximized and has not been effective because there are still problems with evaluation criteria such as effevtiveness, efficiency and adequacy: Effectiveness has not been archieved because the awareness of the texpayer does not carry out the obligation to pay taxes on time , then efficiency has not shown the expected results, this can be seen from the realization that is not in accordance with the target while the adequacy has not shown maximum results, existing infrastructure in the Regional Revenue Office of Central Sulawesi Province is still very limited, this is burdensome to the collection officials because the conditions of the vast and far-reaching regions are not enough to maximize levies. In addition, weak resources, especially the resources of the implementingÂ  apparatus, are directly responsible and carry out the task of finding and identifying potential as sources of regional financial revenue (tax objects).